Workbook for Principles of Microeconomics - Kolmar, Martin (Springer Texts in Business and Economics,, 2018)
This is the companion workbook for the textbook Principles of Microeconomics. Each chapter features a wide variety of exercises, ranging from basic multiple-choice questions to challenging mathematical problems and case study scenarios. The textbook pursues an integrative approach to modern microeconomics by critically reflecting on the main findings of economics from a philosophical standpoint and comparing them to approaches found in the social sciences. It adopts an institutional perspective to analyze the potential and limitations of different market types, and highlights implications for the design of the legal system and business practices throughout. In addition to traditional rational-choice models, important findings from behavioral economics and psychology are also presented.